Hemodynamic effects of size and location of basilar artery fenestrations associated to pathological implications. (30th July 2021) - Tong, Xinyu; Dong, Jia; Zhou, Guojing; Zhang, Xuyang; Wang, Ancong; Ji, Zhi; Jiao, Liqun; Mei, Yuqian; Chen, Duanduan
Abstract: Fenestration is a rare congenital abnormality that refers to a segmental duplication of arteries. It is still not clear about the role of fenestrations in the etiology and pathological evolution of vascular diseases. This study aims to investigate the hemodynamic influence brought by various sizes and locations of fenestration in basilar artery models. A series presumptive fenestration models were established based on a normal basilar artery model with various sizes and locations. Identical boundary conditions were utilized in the computational fluid dynamics simulations and different flow patterns in the fenestration and bifurcation regions were comprehensively analyzed. Wall shear stress (WSS)‐related parameters such as oscillatory shear index (OSI) and aneurysm formation index (AFI) were computed and compared. The value of WSS on fenestration increased by the fenestration's tortuosity, and nearly‐circular fenestration suffered higher WSS than narrow‐strips one. Also, high OSI and low AFI value mainly occurred in the bifurcation region, indicating a high level of turbulence and high risk of aneurysm formation. The location of fenestration mainly changed the impact force of blood flow on the bifurcation and the disorder characteristics of blood flow, while the size of fenestration changed the WSS distribution on the proximal inner wall and bifurcation region of fenestration. In summary, the nearly‐circular fenestration should be stratified carefully which may results in a high risk inducing unfavorable vascular wall remodeling. Abstract : The location of fenestration mainly changed the impact force of blood flow on the bifurcation and the disorder characteristics of blood flow, while the size of fenestration changed the WSS distribution on the proximal inner wall and bifurcation region of fenestration. For further application, this study suggests that the relatively small fenestration with higher tortuosity closed to basilar artery bifurcation should be treated more carefully because of its inherent high risk and adverse impact on bifurcation.